2020
DOI: 10.1124/jpet.120.000004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Morphine-Induced Changes in Signaling at the A3Adenosine Receptor Contribute to Morphine-Induced Hyperalgesia, Tolerance, and Withdrawal

Abstract: ; CNS-central nervous system; CSF-cerebrospinal fluid; CCI-chronic constriction injury of the sciatic nerve; DH-SC-dorsal horn of the spinal cord; DTT-dithiothreitol; EDTA-ethylenediaminetetraacetic acid; EGTA-ethylene glycol-bis(β-aminoethyl ether)-tetraacetic acid; ELISA-enzymelinked immunosorbent assay; HEPES-4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 66 publications
3
32
0
Order By: Relevance
“…In a rodent model, it has been reported that the opioid adverse effects seem to be linked to reduced A 3 ARs signaling. In fact, the stimulation with A 3 AR agonists ameliorates pain sensitivity suggesting that selective A 3 AR agonists may be used in addition to opioids for chronic pain management [ 130 ]. Importantly, it has been reported that the antinociceptive effects of A 3 AR agonists persist at least up to 2 weeks of treatment, suggesting that stimulation of A 3 ARs does not induce tolerance [ 87 ].…”
Section: Ars and Painmentioning
confidence: 99%
“…In a rodent model, it has been reported that the opioid adverse effects seem to be linked to reduced A 3 ARs signaling. In fact, the stimulation with A 3 AR agonists ameliorates pain sensitivity suggesting that selective A 3 AR agonists may be used in addition to opioids for chronic pain management [ 130 ]. Importantly, it has been reported that the antinociceptive effects of A 3 AR agonists persist at least up to 2 weeks of treatment, suggesting that stimulation of A 3 ARs does not induce tolerance [ 87 ].…”
Section: Ars and Painmentioning
confidence: 99%
“…Very recently, it has been demonstrated that the morphineinduced tolerance could also be mediated by the A 3 AR, suggesting a possible use of the A 3 AR agonists as adjuvant therapy in combination with opioids (Doyle et al, 2020). Coadministration of an A 3 AR agonist at a low dose also reduced withdrawal behavior following morphine administration in rats, without reducing morphine's antinociceptive effect.…”
Section: A 3 Adenosine Receptor In Chronic Painmentioning
confidence: 99%
“…The very first hypothesis of a contribution of adenosine receptors in pain was based on the role of the A 1 and A 2A subtypes but, despite their efficacy in preclinical studies, selective agonists could not be included in clinical trials due to significant cardiovascular side effects ( Jacobson et al, 2020 ). Nowadays, the most promising compounds under development are A 3 receptor agonists: preclinical data showed that they are able to revert signaling dysregulation in cancer, autoimmune disorders and different pain conditions ( Doyle et al, 2020 ). When compared to A 1 and A 2A receptors, A 3 receptors have low CNS expression levels, but are highly expressed in human immune and glial cells, including astrocytes, oligodendrocytes, microglia/macrophages and endothelial cells ( Zhang et al, 2016 ), i.e., cell populations that are mostly involved in chronic painful conditions.…”
Section: Purinergic Agents Targeting Glial Cells To Treat Pain: What mentioning
confidence: 99%
“…In fact, Cl-IB-MECA is currently in Phase II clinical trials for hepatocellular carcinoma as anticancer agent, and evidence suggest that activation of A 3 receptors could provide dual benefits in the treatment of a variety of cancer-related pain states ( Jacobson et al, 2020 ). As for chronic pain states, A 3 agonists can be used as a monotherapy or in combination with opioids to improve their safety and efficacy against chronic pain, without reducing opioid’s antinociceptive effects ( Doyle et al, 2020 ). Taken together, available data strongly support the further development of selective A 3 receptor agonists for the treatment of different types of pain syndromes.…”
Section: Purinergic Agents Targeting Glial Cells To Treat Pain: What mentioning
confidence: 99%